Supervised Injecting Room Cohort Study (SIRX): study protocol - Lisa Maher; Thomas Kerr; Matthew Hickman; Alexander Thompson; Peter Higgs; Paul Dietze; Paul A Agius; Nick Scott; Daniel O’Keefe; Mark A Stoové; Jack Stone; Dylan Vella-Horne; et al. (BMJ Open)
Background Supervised injecting facilities (SIFs) are designed to reduce the harms associated with injecting drug use and improve access to health and support services for people who need them. The Supervised Injecting Room Cohort Study (SIRX) aims to provide evidence of the effects, including cost-effectiveness, of a SIF embedded within a community health service, the Melbourne Medically Supervised Injecting Room (MSIR), which has a range of integrated harm reduction, health and social support services on-site.Methods and analysis The SIRX study design involves two prospective cohort studies that collect behavioural data and retrospectively and prospectively linked administrative data for primary and tertiary health services, criminal justice records, and mortality. The two cohorts are: (1) participants drawn from the existing Melbourne Injecting Drug User Cohort Study (SuperMIX; established in 2008–ongoing) through which participants consent to annual behavioural surveys (including serological testing for HIV and hepatitis B and C viruses) and linkage to administrative data; and (2) the SIRX-Registration Cohort (SIRX-R; established in 2024) comprising registered MSIR clients who consent to a baseline behavioural survey and administrative data linkage including the frequency of SIF use, and the uptake of on-site services. Primary outcomes are aligned to the legislated aims of the Melbourne MSIR, including ambulance-attended non-fatal overdoses and all-cause and drug-related mortality. Using causal inference methods, analyses will estimate the effect of MSIR exposure (frequent use/infrequent use/no use) on these primary outcomes. The SIRX study also has a secondary focus on the effect of MSIR exposure on health service use and related outcomes.Ethics and dissemination SuperMIX Study (599/21) and SIRX-R Study (71/23) ethics approvals were obtained from Alfred Hospital Research Ethics Committee. Participants will be assessed for capacity to provide informed consent following a detailed explanation of the study. Participants are informed of their right to withdraw from the study at any time and that withdrawing does not impact their access to services. Aggregated research results will be disseminated via presentations at national and international scientific conferences and publications in peer-reviewed journals. Local-level reports and outputs will be distributed to key study stakeholders and policymakers. Summary findings via accessible outputs (eg, short infographic summaries) for participants will be displayed in relevant services including the Melbourne MSIR and the study van, and distributed via Harm Reduction Victoria.